Epigenetic‐Based Mechanisms of Osteoblast Suppression in Multiple Myeloma Bone Disease. (15th March 2019) - Adamik, Juraj; Roodman, G David; Galson, Deborah L
ABSTRACT: Multiple myeloma (MM) bone disease is characterized by the development of osteolytic lesions, which cause severe complications affecting the morbidity, mortality, and treatment of myeloma patients. Myeloma tumors seeded within the bone microenvironment promote hyperactivation of osteoclasts and suppression of osteoblast differentiation. Because of this prolonged suppression of bone marrow stromal cells' (BMSCs) differentiation into functioning osteoblasts, bone lesions in patients persist even in the absence of active disease. Current antiresorptive therapy provides insufficient bone anabolic effects to reliably repair MM lesions. It has become widely accepted that myeloma‐exposed BMSCs have an altered phenotype with pro‐inflammatory, immune‐modulatory, anti‐osteogenic, and pro‐adipogenic properties. In this review, we focus on the role of epigenetic‐based modalities in the establishment and maintenance of myeloma‐induced suppression of osteogenic commitment of BMSCs. We will focus on recent studies demonstrating the involvement of chromatin‐modifying enzymes in transcriptional repression of osteogenic genes in MM‐BMSCs. We will further address the epigenetic plasticity in the differentiation commitment of osteoprogenitor cells and assess the involvement of chromatin modifiers in MSC‐lineage switching from osteogenic to adipogenic in the context of the inflammatory myeloma microenvironment. Lastly, we will discuss the potential of employing small molecule epigenetic inhibitors currently used in the MM research as therapeutics and bone anabolic agents in the prevention or repair of osteolytic lesions in MM. © 2019 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.